"Há muito tempo, em uma galáxia muito, muito distante...": análise dialético-dialógica do tom/da entonação da equipe autoral de um fanfilme de Star Wars - Nascimento, Natália Rodrigues Silva do (2021)
The main objective of this research is to make a dialectical-dialogical analysis (PAULA; FIGUEIREDO; PAULA, 2011; PAULA, 2013; VILLARTA-NEDER; FERREIRA, 2020) of the verbivocovisual constitution of the fan film “Hoshino - Star Wars Fan Film” (VITALE; CARRASCO, 2016), in order to perceive, through the choices made by the author team, the intonation or the emotional-volitional tone that reveals the project of meaning of the producers of this utterance. This main objective is divided into three specific objectives: 1) to talk about the concepts of gender of speech and utterance from the theoretical point of view of the Bakhtin Circle and, through these concepts, about the field of human activity in which the fan film has life (the fandom), which defines the compositional, thematic and stylistic characteristics of this concrete utterance; 2) to approach the concept of tone or intonation for Bakhtinian theory; and 3) to propose a dialogue between the Circle's conceptions and the concept of verbivocovisuality, in order to have theoretical and methodological subsidies for the analysis of the corpus. In this sense, the present analysis is justified not only because of the relevance that studies on verbivocovisuality have assumed in research in the Bakhtinian field, but also because of the importance of analyzes that assume the dialectical-dialogical bias and that have as their object genres discursive in wide production, circulation and reception nowadays, especially those that are inserted in the digital and technological contexts, such as fan films. The main theoretical basis is concentrated on the work of the scholars of the Bakhtin Circle (BAKHTIN, 2016 [1979]; 2017 [1979]; VOLÓCHINOV, 2017 [1929]; 2019 [1930]), with an emphasis on concepts of speech genres, utterance and intonation/emotive-volitional tone, and the postulations about verbivocovisuality (PAULA, 2014; 2017; PAULA; SERNI, 2017; PAULA; LUCIANO, 2020; LUCIANO, 2021; VILLARTA-NEDER, 2020; VILLARTA-NEDER; FERREIRA, 2020). The auxiliary theoretical basis is composed of studies by Jenkins (2009) on the Culture of Convergence and Participation, in addition to the systematizations of the scholars of the Tártu-Moscou School about the Semiotics of Culture and about the Semiosphere (LÓTMAN, 1979[1973]; 2019[1999]; MACHADO, 2003; VÓLKOVA AMÉRICO, 2012; 2014) and the theories about cinema (JORGE MACHADO, 2016; MUNSTERBERG, 1983; XAVIER, 2005). The dialectical-dialogic discourse analysis (PAULA; FIGUEIREDO; PAULA, 2011; PAULA, 2013; VILLARTA-NEDER; FERREIRA, 2020) is the methodology used in the present research. The present work can contribute to the research of contemporary scholars who focus on the topic of verbivocovisuality based on the studies of the Bakhtin Circle with regard to language, senses and subjects, with emphasis on intonation/tone that are raised through concrete utterances.